Description of Acute Respiratory Infections (ARI) Trends in The High Risk Area Zone of Exposure To Coal Smoke of The Electric Steam Power Plant (ESPP)/PLTU Nagan Raya - Enda Silvia Putri; Susy Sriwahyuni (Universitas Teuku Umar, 2021)
The cases of ARI increase every year after the active operation of the industry. This research aims to explore a description of ARI trends in the high risk zone of exposure to coal smoke of the electric steam power plant (ESPP)/PLTU Nagan Raya. The research method was a combination of cross sectional and phenomology designs. The sample research was 50 people with the criteria for residence 0-50 km from ESPP Nagan Raya with high risk area zone exposure, whilst the technical sample was purposive sampling. The results of this research found an increasing trend for ARI as many as 10% / month during 2019-2020. Chi square test showed P value = 0,000 in which the intrepretation was relationship suspected smoke exposure with symptoms of ARI. Based on in-depth interviews with the community, they experienced respiratory complaints due to the smoke from the ESPP during the establishment of the company, they also complained that their polluted soil and plants were not grown well. To conclude, there was an increasing trend of ARI in the high risk zone of exposure to ESPP smoke and there was relationship between suspected smoke exposure and complaints of ARI, and people were experiencing respiratory complaints.